(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
After the Dobbs landmark decision restored the power to regulate and ban abortion to individual states in 2022, the Supreme Court was called to address reproductive rights once again in 2024. In Food and Drugs Administration v. Alliance for Hippocratic Medicine, anti-abortion groups and some medical professionals demanded a declaration of illegitimacy for mifepristone, the drug used for medication abortions, along with the regulatory framework of the drug, established and updated through time by the Food and Drug Administration (FDA). Although the Justices recognized that the plaintiffs lacked standing without delving into the case’s merits, the importance of scientific evaluations in judicial reasoning is an increasingly relevant matter.